Toddlers Default to Canonical Surface‐to‐Meaning Mapping When Learning Verbs. Issue 3 (30th September 2013) - Dautriche, Isabelle; Cristia, Alejandrina; Brusini, Perrine; Yuan, Sylvia; Fisher, Cynthia; Christophe, Anne
<x xml:space="preserve">Abstract</x> Previous work has shown that toddlers readily encode each noun in the sentence as a distinct argument of the verb. However, languages allow multiple mappings between form and meaning that do not fit this canonical format. Two experiments examined French 28‐month‐olds' interpretation of right‐dislocated sentences (nouni‐verb, nouni) where the presence of clear, language‐specific cues should block such a canonical mapping. Toddlers (N = 96) interpreted novel verbs embedded in these sentences as transitive, disregarding prosodic cues to dislocation (Experiment 1) but correctly interpreted right‐dislocated sentences containing well‐known verbs (Experiment 2). These results suggest that toddlers can integrate multiple cues in ideal conditions, but default to canonical surface‐to‐meaning mapping when extracting structural information about novel verbs in semantically impoverished conditions.